Vibration properties of a timber floor assessed in laboratory and during construction. (1st January 2015) - Jarnerö, K.; Brandt, A.; Olsson, A.
Highlights: Effects from in situ conditions were found to be larger on the damping of a floor than the frequencies. Installation of partitions on the floor has the main effect on frequency. It is likely that the load bearing structure contributes to a major part of the in situ effects of damping. Abstract: Natural frequencies, damping ratios and mode shapes of a prefabricated timber floor element have been assessed experimentally in laboratory with different boundary conditions and in situ (in field) at different stages of construction. In laboratory the change in modal parameters was studied with free-free boundary conditions and simply supported on two sides. Three different simply supported tests with changes in boundary conditions were carried out; the floor placed on the support without any fastening or interlayer between support and floor, the floor screwed to the supports and the floor placed on an elastic interlayer between support and floor. The in situ tests were carried out first on the single floor element and then on the entire floor of the room into which the floor element was built in. The damping ratio of the floor increased from 1% to 3% when simply supported in laboratory to approximately 5% when placed upon a polyurethane interlayer (Sylodyn®) in situ, and to approximately 6% when fully integrated in the building. Thus the in situ conditions have considerable influence on the damping and the values assessed are very high in comparison with damping values suggested in design codes. Regarding natural frequencies it was concluded that the major change in these occur as the floor element is coupled to the adjacent elements and when partitions are built in the studied room, the largest effect is on those modes of vibration that are largely constrained in their movement.